Systematic Review of the use of Depression Anxiety Stress scale 21(Dass-21) in the elderly: Practical applicability across countries (Research, Society and Development, 2024)
The aim was to identify the practical applicability of the Depression, Anxiety and Stress scale (DASS-21) in elderly across countries. Online database searches (EMBASE, PubMed, SciELO) were performed to identify sample characteristics, the purpose of using this scale, and the location of participant recruitment. The search terms included “Aged” OR “Elderly” with the term "dass 21” OR “depression, anxiety, stress scale-21”. The initial data search yielded 855 studies, 833 were excluded. Finally, 22 full-text were analyzed for the study purposes, developed in 13 different countries, including 14,339 participants. The samples were composed predominantly of women, with ages ranging between 60 and 91 years. DASS-21 was used in clinical and non-clinical elderly. The findings have demonstrated that the DASS-21 is useful in monitoring depression, anxiety, and stress in this population across.